1995
DOI: 10.1093/hsw/20.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction among Social Work Discharge Planners

Abstract: Eighty social workers working with elderly patients in 36 acute care hospitals provided information about their overall job satisfaction as discharge planners and identified sources of satisfaction and dissatisfaction in their jobs. Twenty-eight percent were very satisfied and 50 percent somewhat satisfied with their jobs. Sources of satisfaction were the ability to help patients and families, concrete resource provision, job challenge, and autonomy. Dissatisfaction resulted from organizational constraints and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
1
23
0
7
Order By: Relevance
“…This is particularly evident in health care settings, where it may be seen that social work values are not always cost effective. Social workers have little power or control in a physician-dominated authority structure, for example, discharge planning offers a classic example of responsibilit y without decision-making power (Borland, 1981;Kadushin & Kulys, 1995) where expediencies of hospital management frequently require patients to be discharged before they feel ready to leave. The work carried out by social workers is problem centred and often involves choosing between unsatisfactory alternatives (Rushton, 1987).…”
Section: Does Social Work Philosophy and Values Make It Inherently Stmentioning
confidence: 99%
See 3 more Smart Citations
“…This is particularly evident in health care settings, where it may be seen that social work values are not always cost effective. Social workers have little power or control in a physician-dominated authority structure, for example, discharge planning offers a classic example of responsibilit y without decision-making power (Borland, 1981;Kadushin & Kulys, 1995) where expediencies of hospital management frequently require patients to be discharged before they feel ready to leave. The work carried out by social workers is problem centred and often involves choosing between unsatisfactory alternatives (Rushton, 1987).…”
Section: Does Social Work Philosophy and Values Make It Inherently Stmentioning
confidence: 99%
“…Likewise, Kadushin & Kulys (1995) found that social workers experienced conflicting role expectations, that other members of the team did not understand the social work role and did not appreciate what they accomplished. McLean & Andrew (2000) found that stress resulted from role conflict, disagreement about good practice, and lack of recognition.…”
Section: Does Social Work Philosophy and Values Make It Inherently Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, competing values between administrators and social workers can also be a source of stress (Borland, 1981 ;Kadushin & Kulys, 1995).…”
Section: Permanency Planningmentioning
confidence: 99%